Elaboração, implementação e avaliação de um programa de atividade de construção de bonecos para crianças vítimas de violência com dificuldades de aprendizagem. - Silva, Juliana Testa (2006)
The aim of this study was to set up and evaluate an intervention program, based on the manufacture of dolls, with children victims of violence, living in a shelter and presenting learning difficulties. The study aimed also at describing the needs and skills of these children during the proposed activities and their evolution throughout the program. Three children aged seven, eight and nine years, attending the classes of the 1st, 2nd and 3rd grades took part in the program. Doll manufacture involved specific steps so that systematization (patterning) of situations could be assured. Specific strategies were adopted in order to offer opportunities of successful experiences in the tasks performed by the children. The program consisted of 20 hours of intervention, divided in nine videotaped sections. The Silver Drawing Test, applied pre and post-intervention, was used to evaluate the results. To analyze videotape records, an observation guide, previously adapted from clinic observation guide of children, was used. The observation guide allowed systematization of each individual observation, with focus on quantitative performance indexes, by means of production and behavior, facing an oriented situation. Data were analyzed intraperson and results were evaluated to detect possible influences of the program on children performance. pre- and post-intervention SDT indicate differences in child performances. Such differences must be analyzed under the specific context of the program, considering the evolution of behavior and performance, and taking into account the stage of development of each child. In conclusion the program: allowed children an exercise of abilities and a gradual development of autonomy, distinguished the development of initiative attitudes; it supplied chances of organized communication and possibilities affective entailing with the evolution of positive interactions between child and adult; it made possible acquisition and maintenance of attitudes of organization; it allowed the continuous exercise of the planning ability; and the increase on feelings of self-valuation. The program may be used as an instrument to evaluate the presence or absence of the resources necessary to child development, as well to identify areas that must be priority within a stimulation context. A gap to be filled by further research is studies that draw attention to the care of victimized and sheltered children, aiming at overcoming the problems generated by violence, maximizing children internal resources to struggling and raising the factors of protection that provide them with proper self-control when facing risk situations.